2018
DOI: 10.1371/journal.pone.0193494
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uncontrolled blood pressure among Ghanaians: Evidence from a multicenter hospital-based study

Abstract: BackgroundThe burden of uncontrolled hypertension in Low-and-Middle Income Countries (LMICs) is high, with an increased risk of cardiovascular diseases and chronic renal failure in these settings.ObjectiveTo assess the factors associated with uncontrolled blood pressure control in a cross-section of Ghanaian hypertensive subjects involved in an on-going multicenter epidemiological study aimed at improving access to hypertension treatment.MethodsA cross-sectional study involving 2,870 participants with hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 66 publications
11
75
5
2
Order By: Relevance
“…On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV‐negative sample . This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, although the burden of stroke and poor outcomes continue to rise in the subregion due to a myriad of factors hampering the control of key CVD risk factors …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV‐negative sample . This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, although the burden of stroke and poor outcomes continue to rise in the subregion due to a myriad of factors hampering the control of key CVD risk factors …”
Section: Discussionmentioning
confidence: 67%
“…22 This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, 44 although the burden of stroke and poor outcomes continue to rise in the subregion [45][46][47][48] due to a myriad of factors hampering the control of key CVD risk factors. 49…”
Section: Discussionmentioning
confidence: 99%
“…Patients should also be advised to avoid herbal medications and ensure blood pressure is controlled to target with antihypertensive medications and adherence to therapeutic lifestyle interventions. We have previously reported that blood pressure 44 and glycemic control are poor among Ghanaians seeking health care in medical facilities. 45 We have also shown earlier that CKD independently predicts incident stroke among Ghanaians with diabetes and hypertension 46 and that this increased risk may have genetic underpinnings.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have reported rates of 32.9%-49%among similar population groups (2,(14)(15)(16). In Ghana, however, control rates reported are relatively lower and range from 24% to 42% (17)(18)(19). The available studies that have established the high prevalence of uncontrolled hypertension in Ghana, but found inconsistent associations between socio-demographic factors and blood pressure control (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, however, control rates reported are relatively lower and range from 24% to 42% (17)(18)(19). The available studies that have established the high prevalence of uncontrolled hypertension in Ghana, but found inconsistent associations between socio-demographic factors and blood pressure control (18,19). Where client level factors have been assessed, evidence shows poor control associated with the number of hypertensive medications, duration of diagnosis and access to medication (19).…”
Section: Introductionmentioning
confidence: 99%